2009
DOI: 10.3233/jvr-2009-479
|View full text |Cite
|
Sign up to set email alerts
|

Sources of information about multiple sclerosis: Information seeking and personal, demographic, and MS variables

Abstract: Being well-informed about multiple sclerosis (MS) and its treatment is associated with a number of positive clinical and psychosocial outcomes, including higher levels of quality of life and personal control, better coping and adjustment after diagnosis, and reduced dependence on health providers. Understanding the sources from which people with MS seek information is important in assuring that timely, accurate, and useful information is available in a medium and format that is accessible. The purpose of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
3
16
1
1
Order By: Relevance
“…3,13 People with MS most commonly seek health information on the Internet before and after doctor visits. 2,28 While others have found that people with MS do not readily discuss their online searching with doctors, 9,13 we found that discussions of Internet searching with doctors were highly desired. Whether or not patients discuss their use of the Internet is likely dependent on the attitudes of patients towards their information needs, the attitude of health professionals towards online information and the nature of the doctor-patient relationship.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…3,13 People with MS most commonly seek health information on the Internet before and after doctor visits. 2,28 While others have found that people with MS do not readily discuss their online searching with doctors, 9,13 we found that discussions of Internet searching with doctors were highly desired. Whether or not patients discuss their use of the Internet is likely dependent on the attitudes of patients towards their information needs, the attitude of health professionals towards online information and the nature of the doctor-patient relationship.…”
Section: Discussionmentioning
confidence: 71%
“…In fact, while health professionals and MS societies remain important and trusted information sources for people with MS, the Internet is gaining prominence. 2,3 Concurrent with these shifts in treatment and information availability has been a broader move to engage consumers with the evidencebased health movement. 4,5 Evidence-based treatment information is increasingly being provided to consumers online.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Somerset et al[62] und Lejbkowitz et al[47] stellten fest, dass der Arzt und die Krankenschwester die primären Informationsquellen waren. In der Untersuchung von Bishop et al[42] und Poschwatta[61] waren ebenfalls die behandelnden Ärzte die wichtigste Informationsquelle. Solari et al[34] ermittelten den Wunsch nach einer Fachkraft mit der Fähigkeit zur laienverständlichen Sprache als primäre Informationsquelle.Verfügung gestellten Informationen wird ambivalent bewertet.…”
unclassified